A Health Level and Risk Rating Monitoring System of Village Credit Institutions - Karma, I Gede Made; Sulastra, I Made Dwi Jendra; Dewi, Ni Wayan Kurnia (International research journal of management, IT and social sciences, 2022)
As a financial institution that is very vulnerable to negative issues, Bali Governor Regulation No 44/2017, which regulates the management of an LPD (Village Credit Institution) directs that LPDs be managed carefully. Performance indicators that must be considered are the level of health and risk rating of the LPD, which are determined by a number of factors/components related to the financial condition and procedures for managing the LPD. The procedure for determining it is clear, but requires careful calculations and seems difficult for those who do not understand it. Knowledge of the level of health and risk rating will make it easier to find alternative solutions when the LPD has problems. Building a health level and risk rating monitoring system is a solution. The system is built using the Waterfall method with an object-oriented system approach. This system will greatly assist the manager and the supervisory team to maintain good LPD performance, and can quickly anticipate situations that cause the LPD's performance to decline, which is shown from the factors/components of the health level monitoring results and risk ratings by this system.